The Effect of Filler ER4043 and ER5356 on Weld Metal Structure of 6061 Aluminium Alloy by Metal Inert Gas (MIG) - M., Ishak; Nur Fakhriah, Mohd Noordin; Ahmad Syazwan, Kamil Razali; L. H., Shah (Penerbit Universiti Malaysia Pahang, 2015)
Weldability can be defines as the ability of a material to be welded under imposed conditions. Good weldability of aluminum alloys leads to have wide applications in marines, aircraft construction, aerospace and automobile industries. In this study, 6061 aluminum alloys will be joined by using automatic metal inert gas (MIG) welding machine. The filler metal used is ER5356 and ER4043. ER5356 filler contains 5.5% of magnesium and ER4043 filler contains 6% of silicon.